(untitled) (Nigerian Journal of Physiological Sciences, 2022)
This study was designed to investigate the effect of orally administered ethanolic leaf extract of Murraya koenigii on lipid profile of rats fed with cholesterol-enriched diets for 14 days. The study was carried out on 20 male wistar rats divided into 4 groups (n=5). All animals were given ad libitum access to drinking water. Group A was the control group and received normal rat chow, group B received cholesterol-enriched diet (CED); while group C and D received cholesterol-enriched diet and were treated with 200mg and 400mg/kg body weight of ethanolic extract of Murraya koenigii leaf respectively. Blood samples were collected by cardiac puncture on the last day of the experiment for biochemical analysis. Lipid profile was determined by Colorimetric method. Data were expressed as mean ± SEM. Differences in means were compared using ANOVA and Students T-test, P-values ≤ 0.05 were taken as statistically significant. Results showed a significant increase (p ≤ 0.05) in Total cholesterol (TC) level (117.4 ± 4.6) and low density lipoprotein cholesterol (LDL-c) level (50.1 ± 4.7) of group B rats when compared to other groups. The MK (400 mg/kg) treated rats, showed a significant reduction in TC and LDL-c levels, and a significant increase in HDL-c level when compared to CED group. However, there were no significant changes in all the lipid parameters of the treated groups when compared to the control. This study shows that cholesterol-enriched diet causes dyslipidemia and Murraya koenigii exhibited significant hypolipidemic effect on serum TC and LDL-c and increases HDL-c. Hence, Murraya koenigii exhibit antihyperlipidemic properties. Keywords: Murraya Koenigii, hyperlipidemia, Lipid profile, Cholesterol-enriched diet